Resolving multiphoton processes with high-order anisotropy ultrafast X-ray scattering. (10th February 2021) - Natan, Adi; Schori, Aviad; Owolabi, Grace; Cryan, James P.; Glownia, James M.; Bucksbaum, Philip H.
Abstract : Resolving multiphoton processes in strongly excited iodine de novo using high-order anisotropy components in ultrafast X-ray scattering. Abstract : We present the first results on experimentally measured ultrafast X-ray scattering of strongly driven molecular iodine and analysis of high-order anisotropic components of the scattering signal. We discuss the technical details of retrieving high fidelity high-order anisotropy components from the measured scattering data and outline a method to analyze such signals using Legendre decomposition. We describe how anisotropic motions can be extracted from the various Legendre orders using simulated anisotropic scattering signals and Fourier analysis. We implement the method on the measured signal and observe a multitude of dissociation and vibration motions simultaneously arising from various multiphoton transitions occurring in the sample. We use the anisotropic scattering information to disentangle the different processes and assign their dissociation velocities on the Angstrom and femtosecond scales de novo .